Kinetic modeling of methane dehydroaromatization over a Mo2C/H-ZSM5 catalyst: Different deactivation behaviors of the Mo2C and H-ZSM5 sites - Jeong, Jaehun; Hwang, Ahron; Kim, Yong Tae; Hong, Do Young; Park, Myung June (Catalysis Today, 2020)
A kinetic model was developed for the methane dehydroaromatization over a Mo2C/H-ZSM5 catalyst. Because the experimental observations show that the reaction and deactivation simultaneously take place in the catalyst activation (carburization) stage, the initial simulation time was specified as the time at which the activation was completed and the initial activities under each operating condition were estimated. The estimated values show that the initial activity of the Mo2C site is low in the early stage of the catalyst bed, which is probably due to the carbonization, while that of the H-ZSM5 site is very low in the later stage of the bed due to the encapsulation of coupled aromatics caused by the low confinement of Mo2C in the zeolite. Kinetic models were developed for the reaction and deactivation and the kinetic parameters were estimated by fitting the experimental data that were obtained after the activation was completed. The simulated results are in good agreement with the experimental data. The deactivation model indicates a higher temperature dependency of the Mo2C site compared with the H-ZSM5 site. In addition, the benzene and toluene yields abruptly decrease at very high temperature, indicating that a too high temperature should be avoided, although high temperatures are favored because of the endothermic characteristics of the production rate.
Keywords: Benzene and Toluene; Catalyst activation; Deactivation behavior; Initial activity; Kinetic modeling; Methane dehydroaromatization; Operating condition; Temperature dependencies; Deactivation behavior; Initial activity; Kinetic model; Methane dehydroaromatization; Mo2C/H-ZSM5 catalyst